A Tocqueville For the North? André Siegfried and Canada - Kennedy, Sean (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2003)
AbstractThis paper argues that André Siegfried’s writings on Canada played a critical role in shaping his vision of French national identity. Siegfried’s studies of Canada have long been praised for their insight, but recent scholarship has emphasized his role in promoting both anti-Americanism and an exclusionary vision of what it meant to be French during the first half of the twentieth century. For Siegfried, Canada represented a site of managed contestation between British and French culture but also an early example of the deleterious effects of Americanization. His problematic view of French Canada as essentially conservative and unchanging in the face of such challenges reinforced his conviction that France itself should remain true to “traditional” values. The exclusionary implications of his ideas were most evident when Siegfried appeared to accommodate himself to the Vichy regime, but they also persisted after the Second World War.